Task shifting to improve practice efficiency: a survey among general practitioners in non-urban Baden-Wuerttemberg, Germany - Averbeck, Heiner; Rädler, Jasmin; Dhami, Raenhha; Schwill, Simon; Fischer, Joachim E. (European journal of general practice, 2024)
Germany is challenged by an increasing shortage in general practice services, especially in non-urban areas. Task shifting from general practitioners (GPs) to other health professionals may improve practice efficiency to address this mismatch. Exploring GPs’ motives and beliefs towards task shifting in non-urban Germany and identifying potential factors influencing these. The cross-sectional survey was disseminated by mail in three waves between July 2021 and August 2022 among all GPs in non-urban Baden-Wuerttemberg, Germany. It included items on demographics and practice characteristics as well as 15 Likert-scale items addressing motives and beliefs towards task shifting, based on the Theoretical Domain Framework. Likert-scale items were analysed descriptively, influencing factors on motives and beliefs were identified using multiple linear regression. Response rate was 24.2% (281/1162), with respondents comparable in age and gender to all GPs in Baden-Wuerttemberg. GPs’ motives and beliefs towards task shifting are positive overall. The majority expects task shifting to reduce their workload (87.9%) and increase practice efficiency (74.7%). They are open to shift additional tasks to other professionals (69.1%), even in the currently prohibited form of substitution (51.2%). Motives and beliefs were significantly more positive among younger GPs and those participating in the GP-centred care programme. This study describes GPs’ motives and beliefs towards task shifting in non-urban Germany. Identifying younger GPs and those participating in the GP-centred care programme as particularly endorsing may help design future interventions aiming to improve efficiency in general practice in non-urban Germany. The majority of participants, especially young GPs, hold positive motives and beliefs about task shifting in general practice. The GP-centred care programme, as an alternative to the regular remuneration system, influences motives and beliefs towards task shifting. Legal adjustments seem warranted, as GPs support task shifting in the more extensive form of substitution, currently prohibited by law.
Gesehen am 07.04.2025